Defusing the legal and ethical minefield of epigenetic applications in the military, defense, and security context - Dalpé, Gratien; Huerne, Katherine; Dupras, Charles; Cheung, Katherine; Palmour, Nicole; Winkler, Eva C.; Alex, Karla; Mehlman, Maxwell; Holloway, John W; Bunnik, Eline; König, Harald; Mansuy, Isabelle M; et al. (Journal of law and the biosciences, 2023)
Epigenetic research has brought several important technological achievements, including identifying epigenetic clocks and signatures, and developing epigenetic editing. The potential military applications of such technologies we discuss are stratifying soldiers’ health, exposure to trauma using epigenetic testing, information about biological clocks, confirming child soldiers’ minor status using epigenetic clocks, and inducing epigenetic modifications in soldiers. These uses could become a reality. This article presents a comprehensive literature review, and analysis by interdisciplinary experts of the scientific, legal, ethical, and societal issues surrounding epigenetics and the military. Notwithstanding the potential benefit from these applications, our findings indicate that the current lack of scientific validation for epigenetic technologies suggests a careful scientific review and the establishment of a robust governance framework before consideration for use in the military. In this article, we highlight general concerns about the application of epigenetic technologies in the military context, especially discrimination and data privacy issues if soldiers are used as research subjects. We also highlight the potential of epigenetic clocks to support child soldiers’ rights and ethical questions about using epigenetic engineering for soldiers’ enhancement and conclude with considerations for an ethical framework for epigenetic applications in the military, defense, and security contexts.
Veröffentlicht: 13 December 2023
Gesehen am 20.11.2024